Pengaruh Kepemimpinan Transformasional, Komitmen Organisasi dan Burnout Terhadap Kinerja Karyawan: (Studi pada Karyawan Non-Manajerial Hotel Grand Aston Yogyakarta) - Jonathan Christ; Tri Mardiana; Hery Sutanto (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2020)
This study aims to determine (1) The effect of transformational leadership, organizational commitment, and partial burnout on the performance of non-managerial employees at the Grand Aston Hotel Yogyakarta, (2) The effect of transformational leadership, organizational commitment and burnout together on the performance of non-managerial employees Grand Aston Yogyakarta Hotel, (3) Which variable has the most dominant influence on the performance of non-managerial employees at Grand Aston Yogyakarta Hotel. Sampling used in this study is saturated sampling (census), in which all members of the population are sampled. The number of non-managerial employees at Grand Aston Yogyakarta Hotel is 116 people. This study uses a survey method that is research conducted using a questionnaire as a research tool. Data collection by interview and questionnaire was compiled with a Likert Scale and then calculated using the SPSS method. The results of this study are (1) Transformational leadership, organizational commitment, and burnout have a partial effect on the performance of non-managerial employees at the Grand Aston Yogyakarta Hotel; (2) Transformational leadership, organizational commitment and burnout have an effect on together with the performance of non-managerial employees of the Grand Aston Yogyakarta Hotel; (3) Transformational leadership has the most dominant influence on the performance of non-managerial employees at the Grand Aston Yogyakarta Hotel.